Occurrence of gastrointestinal parasites in sheltered dogs at CODEVIDA, Santos-SP: a cross-sectional observational study (Research, Society and Development, 2026)
This study aimed to evaluate the occurrence of gastrointestinal parasites in dogs housed at the Animal Life Defense Coordination (CODEVIDA), in the municipality of Santos, São Paulo. This is a cross-sectional observational study, in which 52 fecal samples collected from kennels housing dogs were analyzed using coproparasitological techniques of spontaneous flotation (Willis-Mollay and modified Sheather) and spontaneous sedimentation (Hoffman, Pons and Janer). Of the 52 fecal samples analyzed, 27 (51.9%) were positive for gastrointestinal parasites. Ancylostoma spp. was the most frequently identified parasite, present in 17 samples (32.7%), followed by Trichuris spp. in 4 samples (7.7%) and Cystoisospora spp. in 2 samples (3.85%). Mixed infections were also observed, including associations between eggs compatible with Taeniidae (Taenia/Echinococcus) and Ancylostoma spp.; Toxocara spp. and Cystoisospora spp.; Giardia spp. and Cystoisospora spp.; and Ancylostoma spp. and Trichuris spp., each detected in 1 sample (1.93%). The results highlight the importance of periodic parasitological monitoring in sheltered dogs.